Open Innovation of Small Business in The City of Medan: Alternative Processes Towards Business Model Innovation - Siregar, Onan Marakali; Marpaung, Nicholas (LifeSciFi, 2024)
Open innovation has become a strategic key element to improve innovation outcomes and commercialization among large companies. However, the relevance and potential of this concept could still be adopted by small-scale companies in Indonesia, especially those facilitated by social media. Research on open innovation for SMEs is limited, but provides important insights. Most research prioritizes in-bound innovation activities and ignores small-scale companies that are often considered radical innovators. Bank Indonesia 2021 data shows 87% of MSMEs were affected by the pandemic, with the majority experiencing a serious drop in sales. Government initiatives to strengthen the resilience of MSMEs through digital transformation have been hampered by low digital literacy. The purpose of this research is to explore the open innovation model for SMEs post COVID-19, especially through digital platforms. The research will focus on SMEs and the empirical analysis is expected to answer research questions on the concept of open innovation, factors influencing adoption, and the readiness of firms' collaboration with external sources. The research method will use descriptive and inferential statistics. The discussion will be supported by relevant literature with theoretical and practical implications.